Pharmacokinetics of intragastric ipriflavone solid dispersion in rats. - Li Ya-ping; Zhou Jian-jun; Zhang Xiang-ying; Pei Yuan-ying (Acta Pharmacologica Sinica, 2016)
AIM: To evaluate pharmacokinetic behavior of ipriflavone solid dispersion in rats. METHODS: The plasma concentrations of ipriflavone in rats were determined by HPLC with UV detector. RESULTS: Plasma concentration-time curves after ig ipriflavone solid dispersion 250 mg.kg-1 in rats were fitted with one-compartment model. Pharmacokinetic parameters were as follows: Ke = 0.21 h-1, T1/2Ke = 5.19 h, Ka = 1.71 h-1, T1/2Ka = 0.41 h, Tmax = 0.67 h, Cmax = 429 micrograms.L-1, AUC = 3916 micrograms.h.L-1; The relative bioavailability of ipriflavone solid dispersion was 323%. CONCLUSION: Ipriflavone in solid dispersion was absorbed more effectively than that in physical mixture in rats.